Subdural Hematoma Following Post-Dural Puncture Headache After Combined Spinal-Epidural Anesthesia for Cesarean Section: A Case Report - Tao, Yifan; Yang, Lu; Lu, Jike (Archives of Clinical and Medical Case Reports, 2025)
Aortic dissection (AD) is a life-threatening condition that can mimic acute myocardial infarction (MI), highlighting the importance of maintaining a broad differential diagnosis in acute chest pain. We present a case of a 43-year-old male with acute chest pain and electrocardiographic findings consistent with ST-segment elevation myocardial infarction (STEMI), including ST elevations in leads V1-V4. Despite elevated troponin levels, classical signs of AD—such as mediastinal widening on imaging and discrepancies in pulse or blood pressure—were absent. Coronary angiography revealed no significant coronary obstruction, but an immediate aortogram identified a dissecting flap at the root of the ascending aorta, just distal to the right coronary artery (RCA) ostium. The patient underwent emergent surgical repair with an uncomplicated postoperative course. This case highlights the critical need for vigilance in atypical presentations of MI and reinforces the importance of incorporating advanced imaging early in the diagnostic process. Prompt recognition of AD in such scenarios is vital, as delays can result in catastrophic outcomes. This report underscores the educational value of recognizing nuanced presentations and integrating multidisciplinary approaches to optimize patient care.